Śāradāpīṭhada māṇikya : Śrī Śrī Candraśēkharabhāratī Svāmigaḷu - Ramachandra Rao, Saligrama Krishna, 1926- (Śāradā Prakāśana, 1983)
Biography of Swami Chandrasekhara Bharati, 1892-1950, Hindu religious leader from Karnataka.